Multivalence of bivariate functionsof bounded index - Nuray, Fatih; Patterson, Richard F. (My University, 2015)
This paper examines the relationship between the concept of bounded index and the radius of univalence, respectively p-valence, of entire bivariate functions and their partial derivatives at arbitrary points in C^2.
Keywords: Entire Function; Bivariate Function; Function of Bounded Index